Tinjauan Etis Teologis Terhadap Tanggung Jawab Pendeta dalam Pelayanan Anak Sekolah Minggu di Jemaat GMIM Bethesda Sagerat Wilayah Bitung VII - Sambouw, Rivaldo A.; Palempung, Rivay B. (Educatio Christi, 2021)
The pastor has the responsibility to preach the word of God, teach, administer the sacraments and guide with the aim of strengthening the faith of the congregation served, so that the pastor has an important role in the formation of the faith of the congregation. The church has a generation of Sunday school children so the ministry of Sunday school children is very important for the future of the church. This study aims to conduct a Theological Ethical study on the responsibility of pastors in the ministry of Sunday school children. The research method used is a case study with data collection based on interviews and observations. The results showed that pastors did not give themselves to Sunday school children's ministry because they were not familiar with Sunday school children's ministry.